Unraveled eaudiobook - Sefton, Maggie (Knitting Mystery, 2011)
Spring is in the air of Fort Connor, Colorado-a time of new beginnings for the House of Lambspun knitters. But for fellow knitter Jennifer's new real estate client, it is his end. He's been murdered and Kelly Flynn is left unraveling a tangle of clues. This may prove to be her most challenging project yet.